Analysis of Goals Scored in European Football Championship with Offensive Parameters of Semi Final Teams 2020/2021 - Zivanovic, Vladimir (Sport - nauka i praksa, 2025)
The study aims to analyze the characteristics of the goals scored in a sample of 51 games and offensive parameters of teams that reached the semi-finals in a tournament held in 2020/ 2021. The analysis of the data used descriptive statistics i.e., the chi-square test and cross tabulation. The results showed statistically significant difference i.e., data that more goals were scored in the second half (83) than in the first (52), x2=7.119, p<0.01. The highest frequency of goals was in the period of 46–60 minutes (30), then 61-75 and 76-90 minutes (24). As for the types of attacks exercised, the highest frequency of goals was found after organized attacks (44.4%), and set plays i.e., corners, free kicks, penalties, and throws–in (when the ball was out of the line of play) (20.7%), x2=11.636, p<0.01, as well as counter-attacks (34.8%), x2=4.813, p<0.05, while the kicks with inside part of the foot ridge (29.6%) were the most frequent. The influence of the first goal scored in the match in relation to the final winning result is expressed by the value (68.8%). Considering the observed positions in the pitch where the goals were scored, the values presented are (48.9%) for areas of 5-11 and 11 meters, (31.1%) for areas of 11-16 and > 16 meters, and (20.0%) for the area of 0-5 meters, with the addition that the forwards scored 73 goals. The semi-finalists showed a percentage of accurate passes per match, in the range value of (82.5-89.3%). The observed parameters and their significance have pragmatic importance in the population of football experts, researchers, and coaches when determining the success and failure of teams in professional competitions.